PROSPECTS AND DANGERS OF BOOTY SLATE GAS IN UKRAINE - Федоришин, Дмитро Дмитрович; Федоришин, Сергій Дмитрович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
This article contains the details about the types of combustible gases and forms of their formation are classified shale formed during the accumulation of sediments. According to the research it is found component and mineral composition of oil shale, their calories specifications. Is shown and proved risks of shale gas development on the example, which were held at the field Barnett Shale (USA).